Urban Latin America
1 online resource
Keywords: "Urban Latin America explores the relationship between images, words and the built environment using an engaging variety of methods and sources, with a timely emphasis on comparative studies. The book brings together scholars with various disciplinary backgrounds and theoretical affiliations who critically approach urban experiences through visual accounts, texts and architectural elements. The reader is introduced to major theories, secondary sources and empirical references that have not been written about in English. Film and photography, fictional and historical writings, particular buildings and landmarks all inspire fascinating glimpses into different moments in the biography of cities in Argentina, Brazil, Chile, Colombia, Ecuador, Mexico, Uruguay and Venezuela."--Provided by publisher.